Rancang Bangun Aplikasi Traffic Counter RFID - Dinan Yulianto; Herman Yuliansyah (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2015)
Referring to the president’s instruction of number 3 in 2004, the transportation department has been given a project to build some managing and controlling shelters for counting and reporting the traffics. Based on an observation of landline transportation from Yogyakarta to Cirebon, the process of vehicles’s computation was done manually by using mechanical timer button, and the result was stored on logbook. This causes a problem since the computation requires rapidity and good physical condition to acquaire the accurate data. In the research, an automatic system of vehicles computation was designed by utilizing the technology of Radio Frequency Identification (RFID). The vehilcles were identified by radio waves emanating from the RFID reader, and the RFID transponder code would be processed into information needed by the user application. The result shows that a system of traffic computation utilizing RFID that is able to process some information automatically to analyze the traffic jam.